2016
DOI: 10.1002/cyto.b.21488
|View full text |Cite
|
Sign up to set email alerts
|

CD44 as a Potential Screening Marker for Preliminary Differentiation Between Congenital Dyserythropoietic Anemia Type II and Hereditary Spherocytosis

Abstract: A distinction between CDAII and HS can be made using the EMA Binding test and anti-CD44 binding. Confirmation of CDAII can subsequently be made based on clinical presentation together with either bone marrow examination or DNA sequencing of SEC23B. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The immunoprecipitation of homozygous erythroblast lysates also showed a strong association between band 3 and HSP70, otherwise known as GRP78, an ER-associated heat shock protein (Figure 9). Another protein that has been suggested as a marker for CDAII is CD44 (Singleton et al, 2018) and we found that CD44 protein is high in SAO RBCs. One difference between SAO and CDAII is the apparent molecular weight of the band 3 protein when separated by SDS-PAGE.…”
Section: Similarities Between Dyserythropoiesis In Sao and Cdaii Cellssupporting
confidence: 55%
“…The immunoprecipitation of homozygous erythroblast lysates also showed a strong association between band 3 and HSP70, otherwise known as GRP78, an ER-associated heat shock protein (Figure 9). Another protein that has been suggested as a marker for CDAII is CD44 (Singleton et al, 2018) and we found that CD44 protein is high in SAO RBCs. One difference between SAO and CDAII is the apparent molecular weight of the band 3 protein when separated by SDS-PAGE.…”
Section: Similarities Between Dyserythropoiesis In Sao and Cdaii Cellssupporting
confidence: 55%
“…For instance, frequent misdiagnosis between CDAI and hereditary stomatocytosis is well known, 69 as well as between CDAII and hereditary spherocytosis, 3 although some screening markers have been proposed. 17,70 Recently, ektacytometry has been used to differentiate between CDAII and hereditary spherocytosis, although some of the values between these conditions show overlap. 71 Differential diagnosis based on a label-free optical marker has also been reported.…”
Section: Diagnostic Workflow Of Cdasmentioning
confidence: 99%
“…Total RNA was extracted from transduced BEL-A2 cells stored in RNAlater, cDNA was prepared and quantitative real-time PCR (qPCR) was used to quantify expression of EMP3 and CD44H RNA, as described in Singleton et al 30 with some modifications. Target gene expression was normalised to the geometric mean of two reference genes and compared with a calibrator sample prepared from untransduced BEL-A2 cells.…”
Section: Methodsmentioning
confidence: 99%